The Dichotomies of the Myth of Europe Laying at the Foundation of our Social Consciousness - LaÃ§i, Irida (Mediterranean Journal of Social Sciences, 2012)
The aim of this paper is to argue that if Europeans wish to become a real Union they should pay more attention to the ethicaland aesthetical values that are deep in the roots of our ancient continent, starting from the mythology. At the very heart of the myth -based story of Europe we find the dynamism of the transformation of our continent, full of beauty, charm, violence, regeneration andhybridization.The story of the â€žMyth of Europeâ€œ should arouse in us the awareness that first and foremost the European race representsa social unity rather than a racial one. While talking about the â€œmythical Europeâ€œ, the dichotomies taken into account aim at stressing thefact that a single united Europe, within the todayâ€™s geopolitical reality, could be founded less on biological and natural factors and in ahigher degree on the living memory, the shared hopes and sufferings, as well as on the self-criticism towards excessive pride and mostof all on the memory of the common myths. Only by recuperating â€œthe defiance of the common symbolsâ€ we could claim our belonging toa Community.